KANDUNGAN FRAKSI SERAT SILASE LIMBAH PISANG (BATANG DAN BONGGOL) DENGAN KOMPOSISI SUBSTRAT DAN LEVEL MOLASES YANG BERBEDA SEBAGAI PAKAN ALTERNATIF TERNAK RUMINANSIA - Andika Mulya; Dewi Febrina; Triani Adelina (Jurnal Peternakan, 2016)
Harvesting bananas will produce stems and stump that can be used as an alternative feed. One processing techniques tomaintain the nutritional value is silage. This study aims to determine the content of the fiber fraction ie. Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), lignin, cellulose and hemicellulose from bananas waste silage with the composition of the substrate and the different levels of molasses.  Research using a Completely Randomized Design factorial pattern with two replications. Factor A : the composition of the substrate, A1. stumps 100% :  stems 0%; A2. 50% stems : 50% stumps; A3. 0% stumps : 100% stems.  Factor B : the addition of molasses  0%; 2.5% and 5%. Data were analyzed using a completely randomized factorial design, the difference between treatments tested Duncan's Multiple Range Test (DMRT). The results showed banana waste silage with the composition of the substrate and molasses with different levels have moderate physical qualities and fiber fractions are NDF 57.86-89.63%; ADF 34.44-46.20%; lignin 11.75-17.19%; cellulose 15.10-32.34%; hemicellulose 11.66-55.18%. Silage that contains 100% of banana stem with the addition of 5% molasses is the best result.